Investigação numérica do campo fluidodinâmico de configurações de jato instalado fortemente integradas com bocais serrilhados - ROCHA, Roberto Thomé da Conceição (2022)
Aeronautical noise is considered the main environmental problem in civil aviation because its directly impacts the people life quality who lives on airports neighborhoods. The harmful effects of this anthropic activity, especially those related to disturb the night sleep, do important airports have their operations interrupted at dawn and impose difficulties to the air traffic expansion. In this regard, it is important to develop effective solutions that reduce the aircraft external noise levels. Currently, mitigation strategies converge on propulsive systems tightly integrated with aircraft structures to improve and reduced noise levels. Thus, the present work carries out a numerical simulation using Computational Fluid Dynamics (CFD) via Reynolds-Averaged Navier-Stokes methodology (RANS) to investigate the flow field from installed jet configurations in combination with a serrated nozzle (SMC006). The simulations were conducted for operating conditions of Mach 0.5 and 0.9, considering different plate extensions and vertical distances in relation to the generated flows, in order to reproduce the installation effects occurring by the interaction between to the exhaust jet with a modern aircraft wing. The results show that the close proximity of the serrated nozzle surface interferes significantly with the flow characteristics, thus improving the understanding of the physical phenomena occurring in tightly integrated jet conditions.